The 2003 CIA World Factbook - United States. Central Intelligence Agency (Salt Lake City, UT : Project Gutenberg, 2008)
"The 2003 CIA World Factbook" by United States Central Intelligence Agency is a reference resource published in 2003. This comprehensive almanac provides concise summaries of demographics, geography, communications, government, economy, and military information for countries and territories worldwide. Produced primarily for U.S. government officials, it draws from numerous federal agencies and public sources. As a public domain work, it has become widely used by researchers and journalists. The Factbook reflects American political perspectives on territorial disputes and sovereignty issues, making it both an essential reference tool and a document shaped by U.S. foreign policy interests. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_World_Factbook
Release date is 2008-12-18
Produced by Al Haines
Keywords: World politics -- Handbooks, manuals, etc; Geography -- Handbooks, manuals, etc; Political science -- Handbooks, manuals, etc; Political statistics -- Handbooks, manuals, etc